Self-perceptual blindness to mental fatigue in mining workers - Purto, Helena; Anabalon, Héctor; Vargas, Katherine; Jara D, Cristian; de la Vega, Ricardo (Frontiers in Neuroergonomics, 2024)
Mental fatigue is a psychophysiological state that adversely impacts performance in cognitive tasks, increasing risk of occupational hazards. Given its manifestation as a conscious sensation, it is often measured through subjective self-report. However, subjective measures are not always true measurements of objective fatigue. In this study, we investigated the relationship between objective and subjective fatigue measurements with the preventive AccessPoint fatigue assay in Chilean mine workers. Subjective fatigue was measured through the Samn-Perelli scale,objective fatigue through a neurocognitive reaction time task. We found that objective and subjective fatigue do not correlate (-0.03 correlation coefficient, p < 0.001). Moreover, severe fatigue cases often displayed absence of subjective fatigue coupled with worse cognitive performance, a phenomenon we denominated Perceptual Blindness to fatigue. These findings highlight the need for objective fatigue measurements, particularly in high-risk occupational settings such as mining. Our results open new avenues for researching mechanisms underlying fatigue perception and its implications for occupational health and safety.